On the three-spaces problem and extension of MLUR norms on Banach spaces - Alexandrov, George (Ann. Sofia Univ. Fac. Math. and Inf., 1994)
We show that if X is a Banach space, Y is a subspace of X which admits an equivalent midpoint locally uniformly rotund (MLUR) norm ||.|| and if X/Y is separable, then the norm ||.|| has an extension which is a MLUR norm on X